Rash decisions can be life-saving: a case of disseminated histoplasmosis in an immunocompromised patient - Huda Naz Khan; Stephen L. Hines; Leigh Hunter (Journal of Community Hospital Internal Medicine Perspectives, 2019)
Histoplasmosis is the most prevalent endemic mycosis in the United States with the highest incidence in the Mississippi and Ohio River Valleys. Most infections are asymptomatic or self-limited. However, in immunocompromised patients, severe and progressive disseminated infection can occur. In our patient, evaluation of her cutaneous lesions was critical in making the diagnosis of acute-disseminated histoplasmosis. Because clinical manifestations of disseminated histoplasmosis can vary widely, early recognition of this infection is challenging. This case highlights the importance of considering histoplasmosis in immunocompromised patients since the untreated disease can be fatal.